Three public relations practitioners in British Malaya - Syed Abdullah Idid, Syed Arabi; Souket, Rizwanah (2019)
The writing of history on the development of public relations has been attributed to specific personalities or events of particular countries that have been made universal and hence ignorant of the position in most of the other countries like Malaysia. The PR history in the US identifies specific personalities like Ivy Lee, Edward Bernays and Arthur Page, while the PR history in the UK talks of two personalities for their influence on public relations- John Grierson (for British documentary) and Stephen Tallents (for publicity and propaganda works). This paper makes a presentation on three early public relations practitioners during British Malaya. The first practitioner was Sir William Taylor who held the post of Agent for the Malay States Information Agency from 1910 to 1920. The second practitioner was George Lamb Peet, who was the Director of the Department of Information from 1939 to 1940. The third was Mervyn Sheppard (aka Mubin Sheppard) who held the post of the Director of the first Department of Public Relations, from 1946 to 1948. The three personalities were chosen for the different political colonial era they served during British Malaya. William Taylor, former Resident General of British Malaya, served the office as Agent in London, while Peet, a former veteran journalist with the Straits Times served his time operating from Singapore. Mubin Sheppard, former District Officer, was operating from his office in Kuala Lumpur. The current study focuses on their contributions and their strategic, big ideas that paved way for the development of the Public Relations Department and later the Department of Information in Malaysia.